PEMIKIRAN AQIDAH AHLUSSUNNAH WAL JAMA’AH SYEKH MUHAMMAD AZHARI AL-FALIMBANI DALAM NASKAH PALEMBANG 1842 - Abdul Azim Amin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: Palembang has been known as a center of maritime Malay - Javanese kingdom since the mid- 17th century AD which has the legislation " Simbur cahaya " breath of Islamic law , has grown even Palembang Darussalam Sultanate and established as a center of Islamic studies and Malay literature ( 1750-1820 ) after the decline of Aceh. At the time of Sultan Mahmud Badaruddin I (1724-1757) , Sheikh appeared Syihabuddin bin Abdillah, as a translator and pensyarah book " Jawahir al-tawhid ", and the period of Sultan Ahmad Najamuddin I (1757-1774), Fakhruddin Pack arose as a writer and translator book " treatise fi al - tawhid " , while Sultan Mahmud Bahauddin period (1774-1804) was born Shaykh al-Falimbany Abdusshomad as the author, and no more. Conditions such as supported by a wealth of natural and human resources . Palembang as a center of Islamic studies in the archipelago which bears some leading scholars until the early 19th century AD, has been attacked, occupied and colonized by the British since the year 1227/1812 to 1816. Subsequently moved into the hands of the Dutch . Resistance to foreign imperialism continued through the war berkobarnya sabil until 1821. Penjajahan can destroy potential Muslims. As a result, many al- ulama and santri Falimbani fall as Martyrs ' hereafter. Some scholars al- Falimbani appear later generations, diantaranta Shaykh Muhammad Azhari ( SMA ) al-Falimbani ( 1811-1874 ). Year 1255/1839 SMA al - falimbani back to Palembang from the land of Hijaz. Then back to Makkah and make up the book of monotheism titled " Athiyaturrahman fi Aqo idyll of Faith " in 1842 . Year 1261/1844 he married Miss Zaliha binti Demat Wirolaksana. After being in-law Jaya Demat Lieu. He returned to Makkah. In this paper the author will reveal patterns of thought Aswaja contained in the manuscript. The methodology used to approach literary study; This method is similar to qualitative research methods , because it prioritizes explanation , description and analysis of an event or process activity. The method also includes documentation; Explores all types of data. The techique in collecting the data by using; observations, interviews, and documentary studies. Then analyzed through three strands: a) flow reduction activities, b ) the presentation of the data flo , c ) verification flow. Keywords : Palembang, Sheikh Alfalimbani, Manuscript, Tawheed